‘Maqashid Al-Sharia’ Perspective for Character Building among Street Children in Makassar, South Sulawesi. - Ipandang Ipandang (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Negative images to street children have raised attention for all those concerned about the street children’s character building. This article discusses three basic problems; the street children reality in Makassar city, fostering and emergence of factors of street children and ‘maqashid al-sharia’ principles on character building for the street children in Makassar, South Sulawesi. In the perspective of ‘maqashid al-sharia’, the position of street children clearly has rules and normative legal basis. Fostering children's character has a fundamental meaning which is the basis of values to change the fate of children, as well as a comprehensive approach to man in spiritual education and noble character. This article meant to emphasize the role of ‘maqashid al-sharia’ perspectives in character building; therefore, street children of Makassar will struggle toward a better future.